Formulation of Transparent Soap with Carrot Juice (Daucus carota L.) as a Skin Moisturizer - Miranza, Nona; Yuniarti, Rafita; Lubis , Minda Sari; Daulay, Anny Sartika (Journal of Pharmaceutical and Sciences, 2025)
Transparent soap is a type of soap that appears clear and attractive, with a finer foam. Carrots are one of the plants that contain compounds that can naturally moisturize the skin. The chemical compounds in carrots that can be used as skin moisturizers are present in high amounts. The aim of this study is to formulate transparent soap using carrot Juice as a skin moisturizer. The transparent soap formulation was made using carrot Juice at concentrations of 4%, 6%, and 8%. The evaluation of the transparent soap formulation included organoleptic testing, moisture content testing, foam height testing, pH testing, irritation testing, and hedonic testing. The results showed that the 8% concentration had the highest moisture content, at 14.45%. The highest foam height measurement was also observed at the 8% concentration, with an average of 8.3. The highest pH level was recorded at 8% concentration, with a value of 9.34. Skin analyzer testing indicated that the highest skin moisture level was achieved at 8% concentration, reaching 48%. The transparent carrot Juice soap met the standards set by the Indonesian National Standard (SNI) in terms of organoleptic properties, moisture content, foam height, pH, skin analyzer results, irritation testing, and hedonic testing. The conclusion of this study is that carrot Juice can be formulated into transparent soap that meets SNI requirements.